Effect of Liners on Microleakage in Class II Composite Restoration - Normaliza Ab. Malik; Seow Liang Li; Normastura Abd. Rahman; Marhazlinda Jamaludi (Univ Kebangsaan Malaysia, 2024)
Indexed by WOS/ Scopus